The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/jhep03(2014)039
|View full text |Cite
|
Sign up to set email alerts
|

Effective lattice Polyakov loop theory vs. full SU(3) Yang-Mills at finite temperature

Abstract: A three-dimensional effective theory of Polyakov loops has recently been derived from Wilson's Yang-Mills lattice action by means of a strong coupling expansion. It is valid in the confined phase up to the deconfinement phase transition, for which it predicts the correct order and gives quantitative estimates for the critical coupling. In this work we study its predictive power for further observables like correlation functions and the equation of state. We find that the effective theory correctly reproduces q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…The drawback is that the effective action is only valid in parameter ranges where the expansion converges, which is currently restricted to the heavy mass region and the confined phase. Even there, the effective theory is unsuitable for long range correlation functions, but it gives accurate results for bulk thermodynamic quantities and phase transitions [12]. In particular, it has already provided predictions with better than 10% accuracy for the critical couplings of SU (2), SU(3) Yang-Mills [8], the critical quark masses where the deconfinement transition changes to a crossover [9] and the tricritical point of the deconfinement transition at imaginary chemical potential [13].…”
Section: Introductionmentioning
confidence: 99%
“…The drawback is that the effective action is only valid in parameter ranges where the expansion converges, which is currently restricted to the heavy mass region and the confined phase. Even there, the effective theory is unsuitable for long range correlation functions, but it gives accurate results for bulk thermodynamic quantities and phase transitions [12]. In particular, it has already provided predictions with better than 10% accuracy for the critical couplings of SU (2), SU(3) Yang-Mills [8], the critical quark masses where the deconfinement transition changes to a crossover [9] and the tricritical point of the deconfinement transition at imaginary chemical potential [13].…”
Section: Introductionmentioning
confidence: 99%
“…This already vastly improves over direct strong coupling calculations of thermodynamic observables [13][14][15]. On the other hand, the missing higher order couplings and long range interactions hamper the applicability of the effective theory to correlation functions and the string tension, where non-local contributions play an increasing role as lattices get finer [12]. The same observation was made with a non-perturbatively determined form of the effective action [9,10].…”
Section: Introductionmentioning
confidence: 78%
“…This is illustrated in figure 3. In [12] we observed that the mis-match of the correlator remains when additional couplings are added in the strong coupling approach, since their leading order contributions are too small. The situation is different with the numerically determined effective couplings.…”
Section: Interaction Terms At Larger Distancesmentioning
confidence: 93%
See 2 more Smart Citations